(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Effendy J. 2022. Isolation and characterization of IbAE7-like 1 gene encoding the cytosolic iron-sulfur cluster assembly pathway in response to skinning injury in sweetpotato. Biodiversitas 23: 4223-4233. Skinning injury is a major constrain in postharvest loss in sweetpotato due to the loss of skin from the surface of the roots. ASYMMETRIC LEAVES1/2 ENHANCER7(AE7) is an important cytosolic iron-sulfur (Fe-S) protein assembly (CIA) pathway. A partial cDNAIbI51 encoding AE7-like 1 was isolated from a skinning injury cDNA library to evaluate its potential role in response to skinning injury. The open reading frameof IbAE7-like 1 consisted of 324 nucleotides and the deduced polypeptide sequences consistedof 108 amino acids with missing 46 amino acid residues at 5? end. The amino acid sequence ofIbAE7-like 1 shared 100% identity toAE7-like 1 previously identified in Ipomoea triloba and Ipomoea nil and 89.91-100% identity from other plants species. The findings indicated that AE7-like 1 was highly conserved in Ipomoea sp. In addition to similarity to AE7-like 1, IbAE7-like 1 also showed similarities to MIP18 (89.91-93.52%); DUF59 (91.67%); FAM96B (90.74%); and proteins with unknown function (90.74-91.67%). IbAE7-like 1 mRNA transcripts showed transient expression in response to skinning injury. The phylogenetic analysis classified IbAE7-like 1 into three main classes. This study revealed IbAE7-like 1 may play a key role in plant defense and wound repair to prevent DNA damage due to skinning injuryin storage roots of sweetpotato.